Replacing Sharīʿa, Ṭarīqa and Ḥaqīqa with Fiqh, Akhlāq and Tawḥīd: Notes on Shaykh Muḥammad Bahārī (d. 1325/1907) and His Sufi Affiliation - Asghari, Seyed Amir Hossein (2020)
Abstract Shaykh Muḥammad Bahārī (1265/1849–1325/1907), aside from being a Shīʿite cleric ( mujtahid ), was a scholar and follower of Sufism. He was a disciple of Mullā Ḥusayn-Qulī Hamadānī (1239/1824–1311/1894) in ʿirfān (gnosis) in the Shīʿī seminary. In his treatise on spiritual wayfaring, Tadhkirat al-muttaqīn , Bahārī represents a triad of jurisprudence ( fiqh ), ethics ( akhlāq ) and monotheism ( tawhīd ). In his terms, fiqh is an introduction to ʿamal (practice), practice is an introduction to the refinement of character ( tahdhīb akhlāq ), and akhlāq is an initial step to tawḥīd (the assertion of God’s unity). This paper examines the intersection of Shīʿī and Sufi spiritual movements within the Shīʿī seminary. It demonstrates that Bahārī sought to reframe mystical thought to present it as more acceptable to the Shīʿī seminary, which was characterized by rigid interpretations of Islamic law. This paper also studies the development of the Ẕahabiyya esoteric school within the Shīʿī seminary by tracing the Sufi chain of Bahārī and his masters.
Keywords: Ẕahabiyya order; Shīʿism; Sufism; Shīʿī seminary; Shaykh Muḥammad Bahārī